A histopathological evaluation of gall bladder cancer with special reference to HER2/neu and E-cadherin in Southern part of Assam - Choudhury, Madhusmita; Choudhury, Gargi Roy; Deka, Monoj K.; Sheikh, Shah A. (International Journal of Research in Medical Sciences, 2021)
Background/Objective: Gall bladder carcinoma (GBC) is an aggressive malignancy with high mortality and aggressive course, with palliation as the only available option. The signs and symptoms of gall bladder arcinoma are not specific and often present late. Diagnosis is, therefore, often made at advanced stage with poorer outcomes. Identifying biomarkers and cancer specific cellular targets, that will pave the way for novel therapeutic approaches and early diagnosis for gall bladder carcinoma, is urgently needed. Proto-oncogenes (HER-2) and E-Cadherin are commonly deregulated in gallbladder cancer (GBC). This study evaluates the prognostic significance of HER-2 and E-Cadherin in GBC patients in Silchar Medical College.Our main objective was to evaluate frequency of HER-2/neu overexpression in GBC and to seek its correlation, if any with conventional clinicopathological parameters and survival. Methods: A total of 168 cases were received and evaluated for Gall Bladder cancer and control specimens were prospectively collected from 2018-2020. Immunohistochemical staining was done using monoclonal antibodies to semiquantitatively evaluate HER-2 and E-Cadherin protein expression. The criterion for HER-2 and E-Cadherin positivity was set at 10% and >5% tumor cells showing complete, membranous staining. Clinicopathological correlations were drawn with major clinical outcomes. Results: It was observed that out of 168 cases the male to female ratio is 1:5 with highest number of cases in the age group of 50-59 , i.e., 70 cases with 41.7%. The most common location in this study was fundus with 69% of cases (116 out 0f 168), most commonly presented as biliary colic with 56 number of cases. Grading was also done in 168 cases where most number of cases were moderately differentiated with 86 number of cases with a percentage of 51%. Expression of Her2Neu and E-Cadherin was evaluated where highest number of cases were seen with 1+ score in the IHC expressions of both the markers with 81 and 61 number of cases respectively. Conclusion: The increasing global incidence, late presentation leading to poor prognosis and lack of effective therapy make the management of gall bladderv carcinoma really challenging. Our study shows the abnormal expression of HER-2 and E-Cadherin expression in gall bladder carcinoma patients in Southern Assam and suggests that these two markers can be used for potential tool for early detection of gall bladder carcinoma and also can be used for targeted therapy in gall bladder carcinoma.